Neonates with Bartter syndrome have enormous fluid and sodium requirements. (31st March 2015) - Azzi, Antonio; Chehade, Hassib; Deschênes, Georges
Abstract Aim Managing neonatal Bartter syndrome by achieving adequate weight gain is challenging. We assessed the correlation between weight gain in neonatal Bartter syndrome and the introduction of fluid and sodium supplementations and indomethacin during the first 4 weeks of life. Methods Daily fluid and electrolytes requirements were analysed using linear regression and Spearman correlation coefficients. The weight gain coefficient was calculated as daily weight gain after physiological neonatal weight loss. Results We studied seven infants. The highest weight gain coefficients occurred between weeks two and four in the five neonates who either received prompt amounts of fluid (maximum 810 mL/kg/day) and sodium (maximum 70 mmol/kg/day) or were treated with indomethacin. For the two patients with the highest weight gain coefficient, water and sodium supplementations were decreased in weeks two to four leading to a significant negative Spearman correlation between weight gain and fluid supplements (r = −0.55 and −0.68) and weight gain and sodium supplementations (r = −0.96 and −0.72). The two patients with the lowest weight gain coefficient had positive Spearman correlation coefficients between weight gain and fluid and sodium supplementations. Conclusion Infants with neonatal Bartter syndrome required rapid and enormous fluid and sodium supplementations or the early introduction of indomethacin treatment to achieve adequate weight gain during the early postnatal period.